IMPROVING THE ABILITY TO WRITE POETRY THROUGH MODELING TECHNIQUES FOR CLASS X STUDENTS OF SMA NEGERI 19 MAKASSAR - Supriadi, Supriadi; Ikram H, Muh.; Tumpu, Abu Bakar; Mulyadi, Mulyadi (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to improve the poetry writing skills of grade X students at SMA Negeri 19 Makassar by applying modeling techniques. Modeling is a learning method that involves a practical approach, where students observe, try, and respond to the actions of teachers or models who are competent in a skill. This study used a qualitative approach with a classroom action research design. The subject of this study was a grade X student at SMA Negeri 19 Makassar who could write poetry that still needs to be improved. The research instrument involves observation, interviews, and portfolio analysis of student poetry writing results. The collected data were qualitatively analyzed to identify changes in the ability to write poetry after applying modeling techniques. The results of this study showed that the improvement in the ability to write poetry through modeling techniques for Class X students of SMAN 19 Makassar has increased. The increase in students' poetry writing skills resulted in 70.74 in cycle 1 and 79.35 in cycle 2.